Financiamento de projetos de cidades inteligentes e sustentáveis nos municípios do estado de São Paulo - Orsatti Filho, Luiz (2022)
This work aimed to research the mainly financial sources and alternative ways of sources for the sustainability smart cities projects implementations in six cities of the São Paulo State (Campinas, Ferraz de Vasconcelos, Guarulhos, Guzolândia, Santo André e São Bernardo). Considering this purpose, exploratory research has done focusing the quality approach on documents of the declare expenses of these cities in the Auditor’s Court of São Paulo State, associate to public expenses of the UN Sustainable Development Goals. It has been possible identify that most of the half of the sources was based on SDG 3, 4 e 11, respectively, Health and Welfare, Education with Quality, Sustainable Cities and Communities, where the SDG 3 was the most representative in financial support, in five of the six researched cities. Considering the analyses of SDG 11, the central objective of this work, it has been detected that the function of the public expenses is associated at Urbanism, following the Transport, excepting Santo André where the Environment Management is the second most representative. After all, this research conclude that exist a low percentual of financial sources for the sustainable and smart cities projects, a few varieties of ways to obtain alternative sources and a deep dependence of the public financial.